THE IMPACT OF SMARTPHONE AND INTERNET USAGE ON ENGLISH LANGUAGE LEARNING - Rosina Fransisca J. Lekawael (English Review: Journal of English Education, 2017)
English language skills here mean the development of the main parts or elements of the language which include speaking, listening, reading, and writing. English language subject has different educational tools that are likely suited with it. Smartphone and internet usage have actively influence daily life, even for children and adolescents. In learning activity, smartphone is a tool to help students connected to be online. A qualitative approach was pursued in this study. Then, the data collection technique used in this study is a survey by using questionnaires. As result, the research shows that most students spend much time to access the social network, some students access internet for dictionary and games, and only a few students access internet for education purposes. In short, the students rather to use smartphone for other thing than education. Therefore, English language learning should be focused on leading language teaching by using English resources from smartphone and internet, as media, which closed to students. By using smartphone and internet, it is expected that either teacher or students become more active and creative to explore their knowledge through media. Pedagogically, there is an urgent need for teachers to implement smartphone-based language learning in order to engage students to be critics with material and its content. So, it enables students to build and enhance a technology awareness of smartphone and internet usage on English language learning in classroom. Keywords: smartphone, internet, English language learning